Coronavirus disease 2019 and acute cerebrovascular events: a comprehensive overview - Zhang, Wanzhou; Ling, Li; Li, Jie; Li, Yudi; Liu, Yajie (Frontiers in Neurology, 2023)
Since the Corona Virus Disease 2019 (COVID-19) pandemic, there has been increasing evidence that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with acute cerebrovascular events such as cerebral infarction, cerebral hemorrhage, and cerebral venous thrombosis. Although the mechanism of cerebrovascular complications among COVID-19 patients has not been adequately elucidated, the hypercoagulable state, excessive inflammation and ACE-2-associated alterations in the renin-angiotensin-aldosterone system after SARS-CoV-2 infection probably play an essential role. In this overview, we discuss the possible mechanisms underlying the SARS-CoV-2 infection leading to acute cerebrovascular events and review the characteristics of COVID-19-related acute cerebrovascular events cases and treatment options available worldwide.